PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN SUB SEKTOR MINYAK DAN GAS BUMI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Raja Julian Lovianda; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to examine partially and simultaneously the influence of corporate social responsiveness and company size on firm value. Where the independent variable in this study is corporate social responsiveness and company size while the dependent variable is the value of the company. The sample used is secondary data derived from the financial statements of oil and gas sub-sector mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2010 to 2015. This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. Data analysis using multiple linear regression analysis, t test, F test, and determination coefficient test. Data analysis using multiple linear regression analysis with SPSS 20. The results of this study indicate that the variables of corporate social responbility in a persial (t test) does not affect the value of the company, while the company size variable affects the value of oil and gas sub-sector mining companies listed in Indonesia stock exchange. Simultaneous test results (f) show no influence of corporate social responbility variables and firm size on the value of the company in oil and gas sub-sector mining companies listed on the Indonesia Stock Exchange.Keywords: Corporate Social Responsibility, Company Size and Company Value